Lactobacillus plantarum synergistically regulates M1 macrophage polarization in resistance against Salmonella enterica serovar Typhimurium infection - Duan, Bingjie; Liu, Ruihan; Shi, Yumeng; Sun, Anqi; Tang, Zhengxu; Wang, Chunfeng; Hu, Jingtao (Frontiers in Microbiology, 2022)
Macrophage polarization affects the progression of pathogenic bacterial infections. Lactobacillus is widely used to interact with macrophages and to exert specific immunomodulatory activities. In this study, we investigated the regulation of macrophage polarization against Salmonella Typhimurium (STM) by Lactobacillus plantarum JL01 (LP), to explore prevention and treatment strategies for salmonellosis. We assessed the in vitro differential polarization of RAW 264.7 macrophages and mouse bone marrow macrophages (BMMs) by LP against STM, by measuring protein and cytokine levels, and bactericidal activity. In addition, we assessed the protective effects of LP against STM by evaluating weight loss, survival, burden of STM in tissues, polarization of macrophages in the spleen and mesenteric lymph nodes (MLNs), intestinal histopathology, and cytokine production. LP slightly affected polarization of RAW 264.7, a slight M1-skewing. LP promoted the RAW 264.7 bactericidal activity against STM. In BMMs, M1 polarization induced by LP was significantly lower than M1-positive phenotype. The combination of LP with M1 synergistically improved M1 polarization and bactericidal activity against STM compared to the individual effects. LP promoted the activation of the NF-кB signaling pathway. Supplementation with the NF-кB inhibitor decreased M1 polarization induced by LP. We observed the protective effect of LP against STM in C57BL/6 mice, through a decrease in weight loss, mortality, STM burden in the liver, and promotion of macrophage M1 and M2 polarization in the spleen and MLNs; though M1 was higher it did not cause inflammatory damage. In summary, LP can synergistically promote M1 polarization in combination with M1 phenotype through the NF-кB signaling pathway, and increases resistance against S. Typhimurium infection. These findings will lay the foundation for the prevention and treatment of S. Typhimurium infections in the future.